Assessment of the Adsorption Activity of Bacterial Cells Using Yersinia pseudotuberculosis Model - R. R. Salikhov; E. M. Kuznetsova; O. A. Volokh (Проблемы особо опасных инфекций, 2024)
Currently, the Russian Anti-Plague Institute “Microbe” produces diagnostic immunoglobulins used in laboratory diagnostics of plague pathogen. One of the important stages in obtaining this category of drugs is the process of adsorption and removal of cross-reacting antibodies to increase the specificity of the drug. For this purpose, inactivated cells of Yersinia pseudotuberculosis strains are used.The aim of the work was to assess the possibility of using immunochemical methods to analyze the adsorption properties of bacterial cells, followed by an assessment of the impact of cultivation method and conditions, and the variant of the strain used on the adsorption properties of bacterial cells.Materials and methods. Cultivation was carried out on solid and liquid nutrient media; cells were inactivated by temperature and chemical exposure. Adsorption activity was assessed using immunoblotting and inhibitory enzyme-linked immunosorbent assay. Statistical processing of the results was performed using two-factor analysis of variance.Results and discussion. The suitability of immunoblotting and inhibitory ELISA methods for qualitative and quantitative assessment of the adsorption properties of bacterial cells has been demonstrated. It has been established that the adsorption properties of bacterial cells are influenced by the method of inactivation and the application of substrate feeding; the method of cultivation does not affect the adsorption properties of cells.